2014
DOI: 10.1088/0953-2048/27/2/025013
|View full text |Cite
|
Sign up to set email alerts
|

Texture in state-of-the-art Nb3Sn multifilamentary superconducting wires

Abstract: The texture of Nb 3 Sn in recent multifilamentary composite wires has been studied by neutron diffraction, synchrotron x-ray diffraction and electron backscatter diffraction. In powder-in-tube (PIT) type superconductors the Nb precursor filaments exhibit a strong 110 fiber texture as a consequence of the severe cold drawing process, and a 110 texture is also observed in the Nb 3 Sn. In the Nb-Ta precursor of the restacked rod process (RRP) strand there is an additional texture component, and in both Ta-alloyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
1
19
1
Order By: Relevance
“…The Nb3Sn elastic anisotropy has been calculated using the grain orientation distribution measured in a PIT wire (billet number B215) produced by Shape Metal Innovation (now Bruker EAS) and in a RRP wire (billet number #7419) produced by Oxford Instruments Superconducting Technology [9]. Cross sections of the PIT wire after 650 °C-120 h heat treatment (HT) and of the RRP wire after 695 °C-17 h HT are shown in Figure 1.…”
Section: Ii1 Nb3sn Composite Wiresmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nb3Sn elastic anisotropy has been calculated using the grain orientation distribution measured in a PIT wire (billet number B215) produced by Shape Metal Innovation (now Bruker EAS) and in a RRP wire (billet number #7419) produced by Oxford Instruments Superconducting Technology [9]. Cross sections of the PIT wire after 650 °C-120 h heat treatment (HT) and of the RRP wire after 695 °C-17 h HT are shown in Figure 1.…”
Section: Ii1 Nb3sn Composite Wiresmentioning
confidence: 99%
“…While in Bronze Route wires the Nb3Sn grains have a nearly random orientation [5,6], we have observed a strong Nb3Sn texture in Powder-in-Tube (PIT) [7] and in Restacked-RodProcess (RRP) type superconductors. As revealed by nondestructive synchrotron X-ray diffraction [8], as well as by Electron Backscatter Diffraction (EBSD) [9], in the PIT wire the Nb3Sn grains have a preferential <110> orientation, while in the RRP wire they have a strong <100> texture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20]. The EBSD/EDX investigations were performed on a FEG-SEM LEO 1530 using an electron energy of 20 keV.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, it was shown by Scheuerlein et al [206] that the grain orientation along the length of a powder-in-tube (PIT) conductor (B215) is preferentially (110) oriented. More recently, an investigation by Scheuerlein et al [207] once again showed that the grain structures of two OST-RRP (billets #7419 and #11976) wires is mainly (100) aligned along the length of the wire, while the grain structure of a PIT wire (B215) is mainly (110) aligned.…”
Section: Superconducting Properties Of High-j C Nb 3 Sn Conductorsmentioning
confidence: 99%